Analisis Critical Path Model yang Digunakan Dalam Manajemen Proyek dan Kontribusinya Terhadap Manajemen Mutu ISO 9001 Di Perusahaan Konstruksi Di INDONESIA - Gugum Gumilar; Koswara Koswara (Institut Sains dan Teknologi Nasional, 2023)
ABSTRACT Critical Path Model (CPM) has been widely used in construction project management as an effective and efficient tool for planning and managing project schedules. This study aims to analyze the contribution of CPM to quality management geothermal project at Lumut Balai, especially in the context of ISO 9001. By reviewing existing literature and case studies, this study explores how CPM can increase the effectiveness and efficiency of ISO 9001 quality management. From the analysis obtained 12 critical paths on the disciplines of Mist Eliminator, Piping, Mechanical, and Painting & Insulation. The results of this study show that the use of CPM can reduce the duration to 604 days compared to the initial schedule of 825 days. CPM can play a significant role in improving quality management in construction companies by providing clear and accurate project schedules, reducing delays, and improving overall project performance. In addition, integration of CPM with quality management tools can enhance overall quality management system and increase chance of project success. The conclusion of this study is CPM has great potential to assist construction companies in increasing the effectiveness and efficiency of ISO 9001 quality management. Construction companies in Indonesia should adopt CPM as a project management tool to ensure project success and meet ISO 9001 quality standards. This study provides insights positive about the future of CPM in construction project management and open opportunities for further research in this field. Keywords: CPM, critical path, quali